Enholding The Relevance Of The Traditional Constitution In Indonesia: A Path To An Integrated National Law - Katjong, Kadir; Polontoh, Herry M.; Yanuaria, Tri (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Customary constitutions in Indonesia are scattered in various regions at the village, sub-district, district, city, province, and even archipelago levels.  The codification and unification of laws are increasingly undermining the existence of customary constitutions in Indonesia.  The existence and position of the customary constitution are increasingly unclear in the regulatory framework in Indonesia. Maintaining the customary constitution is crucial as it can serve as a spirit and guide in the formation of national law.  To remind the nation again about the spirit of being cultured and to give the nation confidence in the nation's civilization, it is necessary that the customary law be placed in an equal position with the existing and recognized statutory order in Indonesia. For this reason, it is necessary to provide a separate place for the growth and development of customary law as part of the nation's wealth and as a reference in the formation of national law so that in every formation of statutory regulations, it always reflects values. is contained in the nation's customs, especially those related to basic law, namely the customary constitution in Indonesia. This paper uses a sociological normative writing method, which will provide an overview of the position and status of the customary constitution in the Indonesian legal system. So it is hoped that through writing this journal, it can provide an understanding of how important the position of the customary constitution is in the development of law in the modern era.Keywords:Position of the Customary Constitution, Indonesian Legal System